2021
DOI: 10.1111/luts.12374
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical bladder wall thickness is a useful marker to predict the postsurgical improvement of symptoms in patients with pelvic organ prolapse‐related overactive bladder

Abstract: Objectives: Pelvic organ prolapse (POP) is a cause of overactive bladder (OAB), and transvaginal mesh (TVM) surgery can improve the symptoms. Bladder wall thickness (BWT) is a useful and safe marker to evaluate bladder function in urinary disorders. The main purpose of this study is to clarify the relationship between BWT and changes in the OAB symptom score (OABSS) after TVM operation in patients with POP.Methods: BWT was measured by ultrasonography before and 6 months after surgery at three sites in the blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In response to the Editorial Comment 1 on our recently published article, 2 we broadly agree with the editor about the importance and promising potential of transvaginal bladder ultrasound (TBU) in the study of certain urologic conditions, such as neurogenic bladder and voiding dysfunctions 3 and, as we report, in the diagnosis of chronic trigonitis in women with recurrent urinary tract infections. 2 In addition to being more comfortable and much less invasive than cystoscopy, TBU can be performed quickly and safely, using a relatively low-cost technology that is already widely accessible, even in Third World countries.…”
Section: Reply Editorial Comments On Transvaginal Ultrasonography For...mentioning
confidence: 77%
See 1 more Smart Citation
“…In response to the Editorial Comment 1 on our recently published article, 2 we broadly agree with the editor about the importance and promising potential of transvaginal bladder ultrasound (TBU) in the study of certain urologic conditions, such as neurogenic bladder and voiding dysfunctions 3 and, as we report, in the diagnosis of chronic trigonitis in women with recurrent urinary tract infections. 2 In addition to being more comfortable and much less invasive than cystoscopy, TBU can be performed quickly and safely, using a relatively low-cost technology that is already widely accessible, even in Third World countries.…”
Section: Reply Editorial Comments On Transvaginal Ultrasonography For...mentioning
confidence: 77%
“…
Recently, a variety of agents, including abiraterone, cabazitaxel, and enzalutamide, have been approved in Japan for patients with metastatic castration-resistant prostate cancer (CRPC). [1][2][3] Some patients, however, have already received all these agents and need a different systemic therapy. The novel agent olaparib (Lynparza, AstraZeneca) is a poly ADP-ribose polymerase inhibitor that was recently approved for the treatment of metastatic CRPC in patients harboring BRCA1/2 mutations.
…”
mentioning
confidence: 99%
“…Similarly, patients with prevalent pelvic organ prolapse exhibit symptoms of the lower urinary tracts, such as an overactive bladder, which may lead to an increase in the thickness of the bladder wall. The bladder's inflammatory response thickened the bladder wall, making the prolapsed vagina irreducible [5]. Bladder calculi should be suspected in firm nodular anterior prolapse that is difficult to reduce.…”
Section: Discussionmentioning
confidence: 99%
“…In female patients with an overactive bladder (OAB) associated with pelvic organ prolapse, we demonstrated that bladder wall thickness, before transvaginal mesh surgery influenced residual postoperative OAB symptoms. 1 In our study, the bladder urine volume was set to <50 mL before transvaginal bladder ultrasound (TBU) examination based on a previous study. 2 The bladder capacity setting at the time of examination is essential because an overextended bladder can lead to an underestimation of the bladder wall thickness.…”
Section: Editorial Comment Editorial Comments On Transvaginal Ultraso...mentioning
confidence: 99%